Exploring EFL Graduate Students' Difficulties in Completing Academic Writing: A Narrative Inquiry - Roja Nur Azizah; Lusi Nurhayati; Ari Purnawan (Universitas Islam Negeri Palopo, 2025)
Academic writing is an essential academic component in higher education. Although EFL graduates have undergraduate writing experience, this does not always imply that the academic writing process will be simpler at the graduate level. At this level, writing requirements grow more complex, including precise language, logical organization, and in-depth analysis, as they are expected to meet the high standards of academic writing inherent in advanced study. As a result, the purpose of this study is (1) to explore the difficulties faced by students in academic writing through students' stories and (2) to investigate the strategies that students apply to cope with difficulties. This study applies a qualitative research method called narrative inquiry research. This research relied on three graduate students in English education as sources, with data acquired through in-depth interviews. The findings revealed that EFL students in higher education struggle with the complexity of academic writing rules, organizing ideas, linguistic barriers, and emotional stress. To overcome this, they employed a variety of strategies, including free writing, seeking feedback from peers or lecturers or utilizing AI tools, regulating emotions, and referring to writing models. In a sense, these findings demonstrate that academic writing is more than just communicating ideas in writing, it is an intellectual and emotional process that may develop the way students think, feel, and express knowledge. Empathetic and supportive learning encourages them to acquire writing strategies while also developing independence, self-confidence, and reflective awareness, all of which serve as the basis for strong and empowered academic writers.